2008
DOI: 10.1248/bpb.31.696
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Peptide, Hirudin, Potentiates the Inhibitory Effects of Stealthy Liposomal Vinblastine on the Growth and Metastasis of Melanoma

Abstract: The metastasis of tumor cells is one of the major obstacles to successful clinical chemotherapy, surgery, and radiotherapy. Accordingly, new therapeutic strategies are needed for overcoming the occurrence of invasion and metastasis of tumor to improve patients' prognosis and survival.The anticoagulants low-molecular weight heparin (LMWH) and recombinant hirudin have shown anti-invasion and antimetastasis effects in experimental models.1,2) However, recombinant hirudin was found ineffective at preventing metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…A previous study suggested that rH had no impact on adhesion to extracellular matrix (ECM) proteins, migration and invasion of in vitro cultured human A375 melanoma cells (10). However, our data clearly showed that rH inhibited Hep-2 cell adhesion to fibronectin, migration and invasion in a dose-dependent manner.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…A previous study suggested that rH had no impact on adhesion to extracellular matrix (ECM) proteins, migration and invasion of in vitro cultured human A375 melanoma cells (10). However, our data clearly showed that rH inhibited Hep-2 cell adhesion to fibronectin, migration and invasion in a dose-dependent manner.…”
Section: Discussioncontrasting
confidence: 53%
“…Thrombin, the key terminal enzyme of coagulation, enhances angiogenesis, stimulates the adhesion of tumor cells to platelet and endothelium, and promotes the growth and metastasis of tumor cells (9). Previous in vitro studies have shown that exogenous thrombin (1 U/ml) acting through its protease-activated receptor (PAR)-1 is capable of enhancing tumor adhesion to platelets, endothelial cells, fibronectin and von Willebrand factor (10). Moreover, exogenous thrombin was shown to promote tumor growth as well as metastasis in experimental animals (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 A dose of 200 g/mouse (ϳ 10 mg/kg) was used because it is the minimal dose others have shown to significantly increase activated partial thromboplastin time and thrombin time in the mouse. 39 As shown in Figure 5, the B-and T-cell responses to FVIII are reduced when mice were treated simultaneously with FVIII and hirudin compared with standard treatment with FVIII only. We also could not detect any nonspecific, toxic, suppressive effects of hirudin in terms of inhibition of mitogenic stimulation of T cells (supplemental Figure 2).…”
Section: Fviii's Immunogenicity Is Linked To Its Ability To Elicit Thmentioning
confidence: 96%
“…A prothrombotic state is characteristic for advanced and metastatic cancers [10,11,16,17], and enzymatically active thrombin is reportedly present on surgically excised tumor specimens, including malignant melanoma [reviewed in 3]. Additionally, hirudin, a highly specific thrombin inhibitor, markedly suppresses tumor seeding into the blood, implantation, and spontaneous metastasis in a mouse model, which prolongs survival [13,[18][19][20]. Several decades ago, pioneering work determined that the Gprotein-coupled thrombin receptor was present on the surface of cancer cells in solid tumors [21], where its contribution to experimental lung metastasis was described [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%